Rancang Bangun Dan Implementasi Sistem Kendali Robot Penanggulangan Bencana Alam Pantai Angin Mammiri Makassar - Nur Alamsyah (Forum Kerjasama Pendidikan Tinggi (FKPT), 2022)
This research aims to produce robots based on Unmanned Aerial Vehicle (unmanned aircraft) as a response to the natural disaster on the coast of Anging Mammiri. Data from the Regional Disaster Management Agency for South Sulawesi Province for victims who drown each year increases. This tool was designed and made to assist beach officers in maintaining the safety of Anging Mammiri beach and minimizing the occurrence of drowning victims due to natural disasters and human error. This research is a type of Research and Development (R&D) research using the ADDIE model. The design of this tool is carried out in 5 (five) stages, namely: analyzing the needs of the robot, determining the design of the robot, developing the robot, implementing the robot and evaluating the robot. As for what was tested in this robot trial were aircraft connections, camera connections, endurance, maneuverability, aerodynamics, flight duration or flight time and endurance tests with air. The results of the robot research function normally and are resistant to water. This robot is very helpful for beach officers to monitor the entire Anging Mammirir beach area remotely using a remote control